-5+2b=3(b-1)

Simple and best practice solution for -5+2b=3(b-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5+2b=3(b-1) equation:



-5+2b=3(b-1)
We move all terms to the left:
-5+2b-(3(b-1))=0
We calculate terms in parentheses: -(3(b-1)), so:
3(b-1)
We multiply parentheses
3b-3
Back to the equation:
-(3b-3)
We get rid of parentheses
2b-3b+3-5=0
We add all the numbers together, and all the variables
-1b-2=0
We move all terms containing b to the left, all other terms to the right
-b=2
b=2/-1
b=-2

See similar equations:

| 4*10-6y=-8 | | 12x^2-13x+9=0 | | 4|x–1|–7=17 | | 17x+8=22x-7= | | H(t)=16t^2+40t+5=0 | | 4m^2-14m-8=0 | | 19x+28=14x+63= | | 3y+25+68=180 | | 25=2x=13+4x | | -4(v+7)=-30-4v | | 2/5x+x+30+3/5x=360 | | 8z-4+3z=-29 | | 2n/3+6=n/4-3 | | 0.80+1x=0.75x+2 | | 0.3333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333333 | | 12=f/0.2 | | 6-6(x+6)+7x=6-8 | | -3(5z-2)-6=-3(7z+5)-3 | | 3y+9=51 | | 3f+4=7f | | 2(a-4)+6a=7a | | 49n^2-40=-4 | | 2x+14=1.50+20 | | -34+7n=8(5n+4) | | 6=7+v/6 | | 2/5x+3/5x+x+30=360 | | 2x+14x=1.50+20 | | 27x-2=12x+73= | | 8r-7+4=18 | | 4y-50=70 | | 28.50x+.75=36.75 | | 2k^2+2k+9=0 |

Equations solver categories